Research on the Response of Urban Sustainable Development Standards to the United Nations Sustainable Development Goals Based on Knowledge Graphs - Maomao Yan; Feng Yang; Huiyao Pan; Chao Li (Land)
In the new era of the vigorous development of digitalization and intelligence, digital technology has widely penetrated various fields. International authoritative standardization bodies, such as the International Organization for Standardization (ISO) and the International Electrotechnical Commission (IEC), proposed a timely new standard concept called Standards Machine Applicable, Readable, and Transferable (SMART) in order to meet this development trend. Its core feature is that the standard can be machine-readable, usable, understandable, and resolvable without human labor so as to achieve the goals of standard formulation, promotion, publicity, and implementation more effectively. Simultaneously, China’s standardization industry is responding to the strategic deployment of “new quality productivity” by actively promoting the digital development of standards and establishing standard information databases, standard formulation management systems, etc., which provide data support and a platform basis for applying new technologies. Advanced technologies such as big data, artificial intelligence, blockchain, and knowledge graphs can be combined with standardization to improve the efficiency of standard development, application accuracy, and implementation effects. To align with these trends, this study focuses on analyzing the responses of national and international standards in the field of urban sustainable development to the United Nations Sustainable Development Goals (UN-SDGs). This study proposes an innovative approach involving the application of knowledge graph technology to the standardization of urban sustainable development and establishing a response correlation between the indicator library for cities’ sustainable development (ILCSD) and SDGs. It also provides additional functions, such as the intelligent extraction of cities’ sustainable characteristic evaluation indicators and aided decision analysis, which greatly enhance the practicability and efficiency of the ILCSD as a technical tool. Based on knowledge graphs, this study analyzes the different responses of important standards in the field of urban sustainable development to the 17 SDGs, accurately identifies weak trends and gaps in standards, and provides a basis for improving the standardization system of urban sustainable development. Simultaneously, by comparing national and international standards and technologies, this study promotes the mutual recognition of standards, which can help China’s urban sustainable development work align with international standards. In addition, the process of establishing and maintaining knowledge graphs facilitates the continuous adoption of new standards through which the indicator library is automatically updated. Finally, in this study, we propose several inspirations for the standardization of urban sustainable development in China, such as an optimization standard system of benchmarking SDGs and a localization application of the original SDG indicators.